Characterization of thermostable alkaline protease from Bacillus halodurans SE5 and its application in degumming coupled with sericin hydrolysate production from yellow cocoon. (March 2019) - Yakul, Kamon; Takenaka, Shinji; Nakamura, Kensuke; Techapun, Charin; Leksawasdi, Noppol; Seesuriyachan, Phisit; Watanabe, Masanori; Chaiyaso, Thanongsak
Graphical abstract: Highlights: Thermostable alkaline serine protease_SE5 showed high specificity to sericin. One step of degumming and sericin hydrolysate production was demonstrated. The protease_SE5 could be a promising candidate for silk industry. Sericin hydrolysate produced by protease_SE5 had antioxidant activity. Abstract: Bacillus halodurans SE5 was newly isolated and grew well on a medium containing crude sericin extract from cocoon. Thermostable alkaline serine protease (protease_SE5) capable of decomposing sericin extract was purified to homogeneity from culture supernatant with a final yield of 25% and 2.01 × 10 4 U/mg. Among the six natural proteins tested, protease_SE5 showed the highest activity toward sericin. The sericin degumming, bio-bleaching coupled with sericin hydrolysate production from yellow cocoon by protease_SE5 and commercial Alcalase were demonstrated in the presence or absence of dithiothreitol (DTT). The addition of DTT enhanced the efficacy of both proteases. However, without DTT, the protease_SE5 had higher degumming ability and produced sericin hydrolysate 4-times higher than commercial enzyme based on the soluble protein concentration. SDS-PAGE and size exclusion chromatography analysis revealed that the maximal concentration of oligopeptides was observed with the hydrolysate prepared by protease_SE5 and showed higher antioxidant activity than those from Alcalase. The appreciable radical scavenging activities of the crude peptide (1.36 ± 0.07 mM) on ABTS, DPPH, and FRAP assay were 1568 ± 78, 3.6 ± 1.6, and 13.6 ± 0.4 μmol TE/L, respectively. Protease_SE5 has potential application for one step degumming and preparation of bioactive peptides from yellow cocoon.